Boosting cancer immunotherapy: drug delivery systems leveraging ferroptosis and immune checkpoint blockade - Zhang, Ting; Gu, Fanlin; Lin, Wei; Shao, Haiyan; Jiang, Aiguo; Guan, Xingang (Frontiers in Immunology, 2025)
Immune checkpoint inhibitors (ICIs) have revolutionized cancer treatment, significantly improving outcomes for various malignancies. Despite their clinical success, only a subset of patients benefits from ICIs treatment, underscoring the need for innovative strategies to enhance their therapeutic potential. Ferroptosis, a unique form of programmed cell death driven by iron-dependent lipid peroxidation, has emerged as a promising partner for enhanced immunotherapy. Combining ferroptosis inducers with immune checkpoint blockade has shown promising potential in improving the efficacy of cancer immunotherapy. This study explores the mechanisms of ferroptosis and immune checkpoint inhibitors for synergistic cancer treatment, and reviews recent delivery platforms integrating ferroptosis and immune checkpoint blockade for enhanced therapy.